2018
DOI: 10.5812/semj.74247
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Fee-Setting for Dental Services in Iran’s Private Sector: Dentists’ Perspective

Abstract: Background and Objectives: In Iran, the private dental sector is the main provider of dental services, however, the price of services that are charged by them is unclear. This study aimed at evaluating the factors affecting fee-setting for dental services delivered by dentists in the private sector and the relative value of services. Methods: In this cross-sectional study, the census sampling method was used among dentists working in the private sector of Kerman city, Iran. The data were collected through a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In addition, studies have shown that people in Iranian households who use dental treatments have a higher likelihood of experiencing catastrophic health expenditure [ 26 ]. In Iran, the private sector provides more than 80% of the country’s dental treatments, and more than 90% of dental treatments costs are paid out of pocket because insurance companies do not cover much due to the limited services covered [ 43 ]. Therefore, the government’s insurance coverage of dental treatments is necessary to prevent catastrophic health expenditures for families with a low economic status [ 44 ].Financing the health system in Iran with insurance comes with challenges that also affect the oral and dental health systems.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have shown that people in Iranian households who use dental treatments have a higher likelihood of experiencing catastrophic health expenditure [ 26 ]. In Iran, the private sector provides more than 80% of the country’s dental treatments, and more than 90% of dental treatments costs are paid out of pocket because insurance companies do not cover much due to the limited services covered [ 43 ]. Therefore, the government’s insurance coverage of dental treatments is necessary to prevent catastrophic health expenditures for families with a low economic status [ 44 ].Financing the health system in Iran with insurance comes with challenges that also affect the oral and dental health systems.…”
Section: Discussionmentioning
confidence: 99%
“…Various factors, including significant price fluctuations of dental materials and equipment over the past 3 years and international sanctions, have led to an increase in the cost of dental services in Iran, thereby influencing dental tariffs. A study highlighted that, factors such as office rent, cost of raw materials, staff salaries, disease severity, and the dentist's skill level, should be considered when determining tariffs [ 32 ]. Despite the recent growth of VHI in low- and middle-income countries, it has not led to a reduction in out-of-pocket healthcare expenditure [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…An investigation in 1991 on dental fees revealed that fees tend to be higher in metropolitan areas than in small cities and that fees tend to be higher in small cities than in rural areas. 23 …”
Section: Discussionmentioning
confidence: 99%